2004
DOI: 10.1038/sj.bjc.6601960
|View full text |Cite
|
Sign up to set email alerts
|

Identification of parathyroid hormone-related protein-derived peptides immunogenic in human histocompatibility leukocyte antigen-A24+ prostate cancer patients

Abstract: Parathyroid hormone-related protein (PTHrP) is a key factor in the development of bone metastases, which are a major barrier in treating prostate cancer patients. In this study, we attempted to identify PTHrP-derived peptides immunogenic in human histocompatibility leukocyte antigen (HLA)-A24 þ prostate cancer patients. Among four different PTHrP peptides carrying the HLA-A24 binding motif, both the PTHrP 36 -44 and PTHrP 102 -111 peptides efficiently induced peptide-specific cytotoxic T lymphocytes from perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 42 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…In light of such consideration, attempts were made to target it in anti-cancer treatments, especially when bone metastases developed. Harada and collaborators, who had identified protein fragments suitable for immunotherapy of HLA-A24 + and HLA-A2 + prostate cancer patients [54,55], in 2005 reported that C-terminal domains of PTHrP could be successfully used also to induce in vitro peptide-specific and cancer-reactive cytotoxic T lymphocytes from blood cells of gastric, colon and cervical cancer-affected patients, which could allow the design of specific vaccines [56]. More recently, the combination of anti-PTHrP treatment and zoledronic acid, a third generation bisphosphonate, was shown to better control the progression of bone metastases in natural killer cell-depleted immunosuppressed mice inoculated with SBC-5 human small cell lung cancer cells than either agent alone, thereby suggesting the usefulness of such dual-target therapy in treating lung tumor-affected patients [57].…”
Section: Conclusion: Pthrp Immunotherapy and Morementioning
confidence: 99%
“…In light of such consideration, attempts were made to target it in anti-cancer treatments, especially when bone metastases developed. Harada and collaborators, who had identified protein fragments suitable for immunotherapy of HLA-A24 + and HLA-A2 + prostate cancer patients [54,55], in 2005 reported that C-terminal domains of PTHrP could be successfully used also to induce in vitro peptide-specific and cancer-reactive cytotoxic T lymphocytes from blood cells of gastric, colon and cervical cancer-affected patients, which could allow the design of specific vaccines [56]. More recently, the combination of anti-PTHrP treatment and zoledronic acid, a third generation bisphosphonate, was shown to better control the progression of bone metastases in natural killer cell-depleted immunosuppressed mice inoculated with SBC-5 human small cell lung cancer cells than either agent alone, thereby suggesting the usefulness of such dual-target therapy in treating lung tumor-affected patients [57].…”
Section: Conclusion: Pthrp Immunotherapy and Morementioning
confidence: 99%
“…The remaining six patients either died from cancer (n = 4) or withdrew from the clinical study (n = 2) before the sixth vaccination. The average number of total vaccinations and vaccinations without any additional therapy were 24.8 (range, 9-50) and 10.9 (range, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…(7)(8)(9)(10)(11) Previous studies have indicated that all peptides can induce HLA-A24 or A2-restricted and tumor-specific CTL activity in PBMCs of cancer patients. (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) For each patient, HLA-type specific peptides were chosen based on the evaluation of both antipeptide IgG levels in plasma and CTL precursors in PBMCs as described previously. (6)(7)(8)(9)(10) Only the reactive peptides (maximum of four) were used for vaccinations.…”
Section: Methodsmentioning
confidence: 99%
“…Cell lines. the cell lines used as target cells for cytotoxicity were the pc3 (hla-a * 2402) and lncap (hla-a * 0201) prostate cancer cell lines, and lncap transfected with the hla-a * 2402 gene (lncap-a24) as previously reported (11). pc3 and lncap-a24 tumor cells were used as relevant A β-tubulin 5-derived peptide induces cytotoxic T lymphocytes restricted to the HLA-A24 allele in prostate cancer patients tumor cells for the measurement of hla-a24-restricted ctl activity, whereas lncap cells were used as irrelevant target cells.…”
Section: Methodsmentioning
confidence: 99%
“…the cell cultures were maintained in rpmi-1640 medium supplemented with 10% FBS. For the pulsing of peptides to the assessed induction of peptide-specific ctls from pBmcs as reported previously (1,8,11), we used c1r-a * 2402 cells (an hla-a * 2402 gene-stable transfectant of the B lymphoblastoid cell line, kindly provided by Dr M. Takiguchi, Kumamoto University, Japan), as reported previously (11,12). RMA-S cells were derived from a mouse mutant cell line deficient in antigen processing, which showed decreased cell surface expression of mhc class i molecules.…”
Section: Methodsmentioning
confidence: 99%